2015
DOI: 10.1016/j.wasman.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Production of pyroxene ceramics from the fine fraction of incinerator bottom ash

Abstract: 16The fine fraction of incinerator bottom ash (IBA) generated from dry discharge systems can be 17 transformed into an inert material suitable for the production of hard, dense ceramics. Processing 22Processed powders show minimal leaching and can be pressed and sintered to form dense (>2.5 g/cm 33The combustion of residual waste in Energy-from-Waste (EfW) facilities is widely used in many 34 developed countries. There are currently 30 EfW facilities operating in Switzerland and ~450 plants in 35Europe. EfW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…BA sorting produces new waste with the further disadvantage that smaller sized grains provide a larger reaction surface and, possibly, higher leaching of heavy metals already present at significant concentrations [14,15,[23][24][25]. Recovery of the smaller fraction of the BA was proposed in regard to pyroxene glass ceramics by heating at a high temperature [26]. However, characterization through different sizes of the BA is required to plan any process of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…BA sorting produces new waste with the further disadvantage that smaller sized grains provide a larger reaction surface and, possibly, higher leaching of heavy metals already present at significant concentrations [14,15,[23][24][25]. Recovery of the smaller fraction of the BA was proposed in regard to pyroxene glass ceramics by heating at a high temperature [26]. However, characterization through different sizes of the BA is required to plan any process of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…5. It appears that the fired density variations between samples were minor, all of them exhibiting values between 1.75 and 1.91 g/cm 3 . Depending on the composition, the maximum density was obtained at different temperatures.…”
Section: Volumic Mass and Water Absorptionmentioning
confidence: 91%
“…They assessed the suitability of MIBA to replace 0, 10, 20, 30, 50, 75, or 100% of natural fine aggregates in masonry blocks (100 mm high × 215 mm wide × 440 mm long) with a design strength of 7 N. The results indicated that MIBA replacement levels below 20% provide adequate compression and tensile strengths with density and absorption also within satisfactory levels [ 17 ]. Bourtsalas et al mixed a fine fraction of MIBA (under 4 mm) with glass and transformed by milling, calcining, pressing, and sintering into high-density ceramics [ 18 ]. In Italy, Schabbach et al demonstrated the obtainment of new ceramics based on a huge amount (60 wt %) of post-treated MIBA and 40 wt % of refractory clay [ 19 ].…”
Section: Introductionmentioning
confidence: 99%